2018
DOI: 10.1177/1971400918781977
|View full text |Cite
|
Sign up to set email alerts
|

Thalamus volume change and cognitive impairment in early relapsing–remitting multiple sclerosis patients

Abstract: Aims The objective of the study was to assess whether changes in the volume of the thalamus during the onset of multiple sclerosis predict cognitive impairment after accounting for the effects of brain volume loss. Methods A prospective study included patients with relapsing-remitting multiple sclerosis less than 3 years after disease onset (defined as the first demyelinating symptom), Expanded Disability Status Scale of 3 or less, no history of cognitive impairment and at least 2 years of follow-up. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…For instance, Amato et al 133 noted that the number of persons with MS with no cognitive impairment decreased from 74% at baseline to 44% at the 10-year follow-up, with a particular increase in the number with mild cognitive impairment (8% to 34%). Increases in the number of persons with cognitive involvement have also been observed at two years, 134 , 149 three years, 115 , 135 four years, 132 five years, 47 , 51 , 60 , 112 , 136 seven years, 31 , 116 and nine years 158 since the initial neuropsychological evaluation.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…For instance, Amato et al 133 noted that the number of persons with MS with no cognitive impairment decreased from 74% at baseline to 44% at the 10-year follow-up, with a particular increase in the number with mild cognitive impairment (8% to 34%). Increases in the number of persons with cognitive involvement have also been observed at two years, 134 , 149 three years, 115 , 135 four years, 132 five years, 47 , 51 , 60 , 112 , 136 seven years, 31 , 116 and nine years 158 since the initial neuropsychological evaluation.…”
Section: Resultsmentioning
confidence: 85%
“…Several studies have found that the SDMT is sensitive to progression, with greater impairments noted over time. 15 , 28 , 60 , 135 , 136 , 143 While declines in attention, processing speed, or memory were detected in several cohorts, 31 , 47 , 60 , 112 , 116 , 134 , 158 this was not observed by Wybrecht et al 50 Instead, they found a greater number of persons with MS impaired in executive functioning 10 years later, particularly on the TMT-B, Digit Spans Backwards, and both phonemic and semantic fluency. 50 Declines in executive functioning, including verbal fluency, have been noted in other longitudinal early MS cohorts.…”
Section: Resultsmentioning
confidence: 90%
“…Especially in Alzheimer's disease, numerous associations have been found between the volumes of cortical and subcortical GM and the development of cognitive impairments (34)(35)(36)(37)(38). Additionally, the volumetric change in at least one GM structure has been linked to cognitive disabilities in normal ageing (39), Parkinson's disease (40)(41)(42)(43), Huntington disease (44), and multiple sclerosis (45). is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 99%
“…Its volume, shape, and function are related to cognitive performance in MS (37)(38)(39). In early RRMS patients (duration of disease <3 years), CI was detected in 28% over a 2-years follow up period, and in this subgroup a significant reduction in the percentage of thalamus volume was observed compared with the cognitively intact group (40). In a large cohort of MS patients, with various forms and stages of the disease, Rocca et al investigated rs-FC abnormalities within the principal brain networks in PwMS (41).…”
Section: Regional Tissue Damage and Atrophymentioning
confidence: 98%